A MIXED INTEGER NONLINEAR MODEL FOR AIR REFUELING OPTIMIZATION TO SAVE FUEL IN MILITARY DEPLOYMENT OPERATIONS - Toydas, Murat; Saraç, Tuğba (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
Fuel is a critical strategic asset for military aviation operations. Air refueling offers both the opportunity to extend aircraft range, and the potential to save fuel by enabling a transport aircraft to depart with less fuel in exchange for additional cargo. We evaluate the practicality of air refueling in terms of fuel savings versus distance and cargo quantity by introducing two non-linear optimization models that examine the tradeoff between departure fuel weight and loaded cargo for given origin, destination, tanker base positions, and freight loads. Our models capture realistic operational procedures of air refueling, and include complex fuel consumption calculations for multiple cargo and tanker aircraft. We optimize initial fuel and cargo amounts, and rendezvous points for air refueling, for multiple cargo and tanker aircraft in a deployment scenario. We use two numerical example scenarios to demonstrate that substantial fuel savings are possible.